2008
DOI: 10.1128/mcb.01651-07
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerase δ Is Preferentially Recruited during Homologous Recombination To Promote Heteroduplex DNA Extension

Abstract: DNA polymerases play a central role during homologous recombination (HR), but the identity of the enzyme(s) implicated remains elusive. The pol3-ct allele of the gene encoding the catalytic subunit of DNA polymerase ␦ (Pol␦) has highlighted a role for this polymerase in meiotic HR. We now address the ubiquitous role of Pol␦ during HR in somatic cells. We find that pol3-ct affects gene conversion tract length during mitotic recombination whether the event is initiated by single-strand gaps following UV irradiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
110
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 47 publications
9
110
0
4
Order By: Relevance
“…6E). This model is further supported by the finding that a weak mutation of yeast Pol-δ causes a reduction in the length of meiotic gene conversion tracts and CO number (15,36).…”
Section: Pol2a Is Not Required For Dsb Formation and Synapsis But Promentioning
confidence: 75%
“…6E). This model is further supported by the finding that a weak mutation of yeast Pol-δ causes a reduction in the length of meiotic gene conversion tracts and CO number (15,36).…”
Section: Pol2a Is Not Required For Dsb Formation and Synapsis But Promentioning
confidence: 75%
“…Pol δ is known as a replicative polymerase that constitutes the replisome (17,18). Genetic studies in yeast indicate that Pol δ is involved in mitotic gene conversion (19), meiotic recombination (20), repair of γ-ray-induced DNA damage (21), and homothallic switching (HO) endonuclease-induced gene conversion (22). Studies of HR in vertebrate systems have shown that translesion polymerases Pol η and Pol ζ also contribute to HR.…”
mentioning
confidence: 99%
“…Genetic and biochemical studies in yeast indicated that both PCNA and Pol δ play major roles in HR (19)(20)(21)(22). Studies in vertebrate systems showed that Pol η and Pol ζ are also involved in HR (23,26).…”
mentioning
confidence: 99%
“…In addition to its roles in DNA replication, Pol ␦ also acts as the gap-filling enzyme in DNA repair processes. Evidence for this has been found in nucleotide excision repair (NER) (14,15), heteroduplex extension during homologous recombination, double strand break repair (16,17), and in translesion synthesis during the switch with translesion polymerases (18) in the DNA damage tolerance pathway (19,20). There is also evidence that Pol ␦ participates in long patch base excision repair (21).…”
Section: Dna Polymerase ␦ (Pol ␦)mentioning
confidence: 99%